2016
DOI: 10.1080/08997659.2016.1159620
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the Fathead Minnow Nidovirus from Muskellunge Experiencing Lingering Mortality

Abstract: In 2011, the Fathead Minnow nidovirus (FHMNV; Genus Bafinivirus, Family Coronaviridae, Order Nidovirales) was isolated from pond-raised juvenile Muskellunge Esox masquinongy suffering from lingering mortality at the Wild Rose Hatchery in Wild Rose, Wisconsin. Moribund Muskellunge exhibited tubular necrosis in the kidneys as well as multifocal coalescing necrotizing hepatitis. The FHMNV was also isolated from apparently healthy juvenile Muskellunge at the Wolf Lake State Fish Hatchery in Mattawan, Michigan. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Our findings clearly demonstrated that baitfish obtained from retail bait vendors harbor OIE‐notifiable and baitfish‐associated viruses that are not only infectious to cyprinids but also to a wide range of other fish species (Faisal et al. , ). Surprisingly, some of the infected fish exhibited pronounced external signs of disease and yet remained for sale, with the possibility of ultimately finding their way into numerous waterbodies.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Our findings clearly demonstrated that baitfish obtained from retail bait vendors harbor OIE‐notifiable and baitfish‐associated viruses that are not only infectious to cyprinids but also to a wide range of other fish species (Faisal et al. , ). Surprisingly, some of the infected fish exhibited pronounced external signs of disease and yet remained for sale, with the possibility of ultimately finding their way into numerous waterbodies.…”
Section: Discussionsupporting
confidence: 54%
“…The Muskellunge is one such species that is fed baitfish in hatcheries and has proven susceptible to both VHSV and FHMNV (Faisal et al. , ). As a consequence, this practice may expose a highly susceptible fish species to potentially lethal, debilitating viral infections, and widespread stocking of these fish may lead to further expansion into new geographic areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The order Nidovirales was defined by the International Committee on Taxonomy of Viruses (ICTV) at the X th International Congress of Virology in Jerusalem in 1996, and currently includes four virus families: Arteriviridae, Mesoniviridae, Roniviridae and Coronaviridae, the latter being divided into the sub-families Coronavirinae and Torovirinae. Nidoviruses infect diverse host species ranging from mammals to birds, fish, crustaceans and insects (Blanck and Ziebuhr, 2016;Faisal et al, 2016;Wernery et al, 2016;Wickramasinghe et al, 2011;Zeng et al, 2016). Despite considerable diversity in terms of genome size and virion morphology, nidoviruses have been grouped together in the same virus order based on their similar genome organization, a conserved set of domains and enzymatic functions in their replicase polyproteins, and their unique transcription strategy that results in production of a set of nested (Latin nidus; nest) subgenomic mRNAs (Gorbalenya et al, 2006).…”
mentioning
confidence: 99%